2016
DOI: 10.1002/star.201600152
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, functional properties, and digestion of isolated starches from pigmented chickpea (Cicer arietinumL.) cultivars

Abstract: This research was undertaken to study physicochemical, functional, and in vitro starch digestion properties of wet‐milled chickpea starches obtained from an array of ten cultivars differing in seed coat color (black, brown, green, red, and cream). The yield of chickpea starches ranged from 19.22 to 30.06%, in which resulting starches varied in total starch and amylose contents from 87.14 to 96.02% and 25.05 to 35.26%, respectively. The DSC transition temperatures To, Tp, and Tc and gelatinization enthalpy rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
4
10
0
Order By: Relevance
“…It was reported that the hectoliter weight of the blue corn sample was 87.46 kg/100 L (Somavat and others ). Additionally, in a study hectoliter weight of 15 blue maize genotypes was reported between 71.07 and 83.92 (Milán‐Noris and others ) and in this study it had higher hectoliter weight value than that of these blue maize's genotypes.…”
Section: Resultssupporting
confidence: 61%
“…It was reported that the hectoliter weight of the blue corn sample was 87.46 kg/100 L (Somavat and others ). Additionally, in a study hectoliter weight of 15 blue maize genotypes was reported between 71.07 and 83.92 (Milán‐Noris and others ) and in this study it had higher hectoliter weight value than that of these blue maize's genotypes.…”
Section: Resultssupporting
confidence: 61%
“…Moreover, the HI and pGI ranged from 81.52 (B.4418) to 88.96 (C.BS) and from 78.47 (B.4418) to 84.88 (C.BS), respectively. These values were higher compared to their corresponding pGI values assayed in refined cooked starches (Milán‐Noris et al ., ). According to the observed pGI values, cooked chickpea flours can be classified as high glycemic impact foods (Jenkins et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Lower values have been reported in chickpeas (0.2% and 0.9%; Genç et al ., ; Maccaferri et al ., ). In a previous study with the therein chickpea cultivars (Milán‐Noris et al ., ), desi cultivars with coloured seed coats showed higher amounts of coats (9.9–13.6%) compared to the cream‐coloured cultivars (3.6–4.1%). A similar trend was observed in β‐glucans assayed in the different chickpea flours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, pulse seeds are on the spotlight of food industry, mostly due to its functional and nutritional properties. Among them, chickpea (Cicer auretium) has received special attention because the crop is high yielding and is considered as staple food in many Eastern countries (Du et al, 2014;de la Rosa-Millan et al, 2017;Ch avez-Murillo et al, 2018;Mil an-Noris et al, 2019). This pulse crop often presents higher protein content when compared with others, as well as a relative higher proportion of carbohydrates, in which starch and b-glucans play a significant role in their functional and nutritional properties; particularly their low glycemic response (Chung et al, 2008;Rachwa-Rosiak et al, 2015).…”
Section: Introductionmentioning
confidence: 99%